2011
DOI: 10.1080/01904167.2011.580820
|View full text |Cite
|
Sign up to set email alerts
|

RE-GREENING OF LYCHEE (LITCHI CHINENSISSONN.) LEAVES WITH FOLIAR APPLICATIONS OF IRON SULFATE AND WEAK ACIDS

Abstract: 2 Lychee (Litchi chinensis Sonn. cv. 'Mauritius') trees growing in calcareous soils are prone to iron (Fe) deficiency, typically prevented by soil application of chelated Fe, which is very expensive compared to iron sulfate (FeSO 4 ). Therefore, the effects of foliar applications of weak acids (ascorbic or dilute sulfuric acid), weak acids plus FeSO 4 , or a soil drench of chelated iron (Fe-EDDHA) on leaf chlorophyll index, leaf ferrous iron (Fe 2+ ) and total Fe concentrations, leaf gas exchange and plant dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…In lychee leaves, foliar application of FeSO 4 either alone or in combination with acid and surfactant as well as with soil applied Fe-EDDHA leads to high leaf Fe 2+ concentration. Total Fe concentration was higher than 110mg/kg DW in lychee plants with foliar application of FeSO 4 (Schaffer et al, 2011).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In lychee leaves, foliar application of FeSO 4 either alone or in combination with acid and surfactant as well as with soil applied Fe-EDDHA leads to high leaf Fe 2+ concentration. Total Fe concentration was higher than 110mg/kg DW in lychee plants with foliar application of FeSO 4 (Schaffer et al, 2011).…”
Section: Discussionmentioning
confidence: 85%
“…All plants in foliar application of FeSO 4 were greener (Schaffer et al, 2011). Likewise, foliar application of FeSO 4 to pear trees improved the leaf chlorophyll content either due to the better activity of enzyme ferric chelate reductase after oxidation of foliarly applied Fe 3+ to Fe 2+ or the direct uptake of Fe 2+ (Álvarez-Fernández et al, 2004).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Natural amino acids are very small molecules that chelate with micronutrients are quickly absorbed, translocated and metabolized by plants. The merits of amino acid chelates are that the amino acid ligand frame and defend the micronutrients from adverse relations usually take place in soil solution, in the presence of soil or on leaf surfaces (Schaffer et al, 2011). Various examinations have demonstrated that the likely limit of iron compounds to address iron lacks in plants developed in alkaline and calcareous soils relies upon two fundamental features (Chaney and Bell, 1987) viz.…”
Section: Introductionmentioning
confidence: 99%
“…These amino acid chelated micronutrients are exactly used for foliar spraying and soil application. Schaffer et al (2011) [16] examined that the natural amino acids are very small molecules they chelated with micronutrients therefore they are quickly absorbed, translocated and metabolized by plants. The merits of amino acid chelates are that the amino acid ligand frame and defend the micronutrients from adverse relations usually those take place in soil solution, in the presence of soil or on leaf surfaces.…”
Section: Introductionmentioning
confidence: 99%